1984
DOI: 10.1016/0014-5793(84)80778-4
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of bioactive β‐endorphin processing in rat pars intermedia

Abstract: Acid extracts of rat pituitary neuro-intermediate lobes have been shown by ion-exchange chromatography and radio-immunoassay to contain predominantly the inactive derivatives of /3-endorphin, a,N-acetyl B-endorphin l-27 and a,N-acetyl fl-endorphin l-26; the biologically active form, fl-endorphin 1-31, is a minor component. In contrast, it was found that fi-endorphin generated in neuro-intermediate lobe cells in monolayer culture was less processed: the principal peptides related to bioactive B-endorphin l-3 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…With this procedure it became apparent that the patterns of |5-endorphin-related peptides released from rat anterior pituitary cells can vary according to whether secretion takes place under basal or stimulated conditions and whether the secretion is chronically inhib ited. As previously reported [11] acute stimulation o f ante rior pituitary cells with C R F leads to an increase in the release o f immunoreactive [i-endorphin, with a particularly marked increase in 3.5-kilodalton (f-endorphin relative to lipotropin. In the present experiments it is shown that con tinuing incubation with C R F over a period of time ( > 5 h) leads to a preferential release of lipotropin and it is accom panied by only small amounts of [f-endorphin.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…With this procedure it became apparent that the patterns of |5-endorphin-related peptides released from rat anterior pituitary cells can vary according to whether secretion takes place under basal or stimulated conditions and whether the secretion is chronically inhib ited. As previously reported [11] acute stimulation o f ante rior pituitary cells with C R F leads to an increase in the release o f immunoreactive [i-endorphin, with a particularly marked increase in 3.5-kilodalton (f-endorphin relative to lipotropin. In the present experiments it is shown that con tinuing incubation with C R F over a period of time ( > 5 h) leads to a preferential release of lipotropin and it is accom panied by only small amounts of [f-endorphin.…”
Section: Discussionsupporting
confidence: 64%
“…In contrast, under basal condi tions it has been reported that less processed intermediates appear to predominate [2,12,15,22]. More recently it has been shown that in response to dopamine blockade rat neuro-intermediate lobe cells produce a higher proportion o f the more heavily processed forms o f (1-endorphin; in the absence of dopamine the cells generate bioactive P-endor phin as the major peptide [11]. In other studies pulse chase experiments carried out in the frog neuro-intermediate lobe have demonstrated that a -M S H (ACTH 1-13) is elaborated in the inactive des-acetyl form but on stimulation o f secre tion the acetylated peptide is released into the extracellular medium [17], These lines o f evidence indicate that during dynamic secretion the processing o f pro-opiomelanocortin (PO M C) is altered, apparently to generate higher levels of bioactive peptides.…”
mentioning
confidence: 98%
“…The results seem to indicate that the form of processing of the TRH prohormone in the hypothalamus is different from that in the spinal cord, but it should be realised that variations in processing can occur within a single tissue. Intratissue variations have been reported for j-endorphin processing in rat pars intermedia, associated with the regulatory influence of dopamine [18], and it is possible that similar variations may occur in the processing of TRH.…”
Section: Discussionmentioning
confidence: 98%
“…It is thus possible that an explanation for the redundancy of the innervation may yet be found at the postsynaptic level in some differential effects of the transmitters on other functional parameters in the melano trophs, for example, gene expression, or synthesis or posttranslational processing of the secretory products. GABA, for in stance, has been observed to inhibit expression of the proopio melanocortin gene [37], And dopamine has been seen to inhibit the synthesis of proopiomelanocortin [38], and also the acetyla tion of both [Vendorphin [39,40] and «-melanocyte stimulating hormone [41,42]. But conjectures on possible differential ef fects at the postsynaptic level must confront the indications that the intracellular signals set in motion by the three transmitters in the melanotrophs appear, from current evidence, from me lanotrophs and other cells, to be similar, each involving re ductions in cyclic AMP and cytosolic Ca2+; and furthermore, that these same intracellular signals have been implicated in the regulation of gene expression and posttranslationai processing [43,44].…”
Section: Discussionmentioning
confidence: 99%